Urinary CC16 levels in winter versus summer sport athletes after eucapnic voluntary hypernoea - Bolger, C.; Tufvesson, E.; Stenfors, N.; Devereux, G.; Ayres, J. G.; Holmberg, H. C.; Bjermer, L.; Sue-Chu, M.; Kippelen, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Exercise-induced bronchoconstriction (EIB) is highly prevalent in elite athletes, especially in those training in cold dry environments (1). Dehydration of the airways plays a key role in this process (2). EIB has recently been linked to airway epithelial injury in asthmatic individuals (3). The aim of the study is to determine whether a short period of hyperpnoea of dry air causes airway epithelial disruption in winter and/or summer sport athletes. We hypothesise that urinary level of the Clara cell protein (CC16) - an indirect marker of permeability/cellular integrity of the lung epithelial barrier (4) - will be increased after a eucapnic voluntary hyperpnoea (EVH) test and that this increase will be larger in winter compared to summer athletes. Forty two female athletes - 28 summer athletes (age 31.1+/-1.7yr (SEM), training volume 9+/-1.1h/wk) and 14 winter athletes (age 21.4+/-0.8yr, training volume 12.0 ± 1.10h/wk) - took part in this study. They all performed an 8-min EVH test at a target ventilation rate of 30 times their baseline forced expiratory volume in one second (FEV1). After the challenge, FEV1 was measured in duplicate at 2, 5, 10, 15, 20, 30, 60 and 90min. A sustained decrease in FEV1 of at least 10% from baseline was considered positive. Urine samples were collected at baseline and at 30, 60 and 90min recovery. CC16 concentration was measured by enzyme immunoassay. Ten summer athletes had a positive test (max FEV1 fall = 19.6+/-2.4%), whilst eighteen of the summer athletes and all the winter athletes were negative (max FEV1 fall = 5.7+/-0.7% and 5.3+/-0.7%, respectively). CC16 increased significantly after the challenge in all three groups (P<0.01) with no difference between groups: delta CC16 (max post-EVH minus baseline) in summer EVH negative athletes was 0.241+/-0.1 ng/µmol creatinine, 0.292+/-0.085 ng/µmol creatinine in summer EVH positive athletes, and 0.123+/-0.047ng/µmol creatinine in winter EVH negative athletes (P=0.415). In conclusion, a short period of hyperpnoea of dry air is associated with an increased rate of CC16 excretion in urine in both winter and summer athletes. This suggests that the integrity of the airway epithelium might be compromised by loss of airway surface lining fluid when athletes inhale dry air at high flow rates. This appears to occur irrespective of the degree of bronchoconstriction or regular training environment.